DARK MATTER SCALING RELATIONS AND THE ASSEMBLY EPOCH OF COMA EARLY-TYPE GALAXIES - Thomas, J; Saglia, R; Bender, R; Thomas, D; Gebhardt, K; Magorrian, J; Corsini, E; Wegner, G (Institute of Physics Publishing, 2009)
Axisymmetric, orbit-based dynamical models are used to derive dark matter scaling relations for Coma early-type galaxies. From faint to bright galaxies, halo core radii and asymptotic circular velocities increase. Compared to spirals of the same brightness, the majority of Coma early-type galaxies - those with old stellar populations - have similar halo core radii but more than two times larger asymptotic halo velocities. The average dark matter density inside 2 r eff decreases with increasing luminosity and is 6.8 times larger than in disk galaxies of the same B-band luminosity. Compared at the same stellar mass, dark matter densities in ellipticals are 13.5 times higher than in spirals. Different baryon concentrations in ellipticals and spirals cannot explain the higher dark matter density in ellipticals. Instead, the assembly redshift (1 + z) of Coma early-type halos is likely about two times larger than of comparably bright spirals. Assuming that local spirals typically assemble at a redshift of one, the majority of bright Coma early-type galaxy halos must have formed around z 2-3. For about half of our Coma galaxies, the assembly redshifts match with constraints derived from stellar populations. We find dark matter densities and estimated assembly redshifts of our observed Coma galaxies in reasonable agreement with recent semi-analytic galaxy formation models. © 2009. The American Astronomical Society. All rights reserved.